Strategi Sosialisasi Penjualan Sebagai Solusi Pengembangan UMKM di Desa Pasir Jaya - Fauziah; Kamaruddin, Muhammad Junaid; Galuh Sukmaranti; Harisuddin; Sinaga, Andre Frianto; Dewi, Maharani; Zahra, Nabila; Farhah, Nabilla Fitri Assy (MJK PUBLISHER, 2025)
The real need is that MSME actors need a wider range of purchasing their products, not only in the surrounding environment. This is a real need that inspires and provides the background for community service implementation activities in the form of socialization of sales strategies. In this article, the method used is the consultation method. The consultation method is a method that is carried out by providing material to the audience regarding problems about sales strategies given by lecturers. The results of the marketing strategy socialization activity in Pasir Jaya Village were carried out smoothly and received a good response from the community. Participants who attended included MSME actors, youth groups, and village officials. Through this activity, the public's understanding of the importance of marketing local products is increasing. They began to recognize various promotional approaches, such as the use of social media, attractive packaging designs, and the application of prices that suit market needs.